Job Satisfaction Among Workers In Automobile Industry In Malaysia - Philomena, Rajenderam (2011)
The study addressed the significant factors affecting the workers in the automotive industry in Malaysia. The research identifies the differences of the influencing factors based on gender and reporting structure.